ANALISIS PENGGUNAAN APLIKASI TANYA SAJA SEBAGAI MEDIA KONSELING KEBIDANAN: STUDI CROSS-SECTIONAL - Irma Yanti; Lilis Suryani; Riska Setiawati; Leni Suhartini (HSG (Health Science Growth) Journal, 2022)
The best choice for the public in promotive and preventive efforts during the Covid-19 pandemic is done online. The "Tanya Only" application is an android-based midwifery counseling media that can provide information about maternal and child health. This study aims to determine the characteristics and interests of using the "Tanya Only" application. This study used a cross sectional method with data collection carried out in July-December 2021 at the Posyandu Puskesmas Tanjupura Karawang. Respondents are all mothers who come to Posyandu who have smartphones and have downloaded the “Tanya Only” application, totaling 57 respondents. Data analysis using chi square with a significance level of 5%. The results showed that the average user of the "Tanya Only" application was 33 years old, had a high school education background of 50.9% and had an interest in using the "Tanya Only" application as much as 81.1%. Variables related to the use of the "Ask Only" application were the respondent's age (p 0.015) and interest (p 0.000) while the education variable had no relationship with application use. Counseling media during the Covid-19 pandemic can use the "Ask Only" application.